Creation and relations—A sami perspective on Scandinavian creation theology. Issue 2 (20th May 2021) - Webber, Torbjørn Brox
Abstract: From a Sami perspective, this article discusses how Scandinavian creation theology can support a stronger resilience against that which threatens the creation in all its variations. Sápmi is the land of the Indigenous Sami people in the northern part of Scandinavia and Kola penisiluania in Russia. During the 19th and 20th century the Norwegian part of Sápmi was colonized in the so‐called Norwegianization project. Today we see an increasing battle around natural resources. The article briefly depicts Sami indigenous theology, which emphasizes the circle of life, creation, and humanity's relationship within the creation and its Creator. It then presents several basic features of Scandinavian creation theology that highlight the egalitarianism surrounding the creation and how all people stand in relation to this with an ethical obligation to defend life where it is threatened.